(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The article aims to analyse Ethiopia’s climate policies and the country’s positioning in international forums by exploring the narratives constructed with climate change mitigation and adaptation strategies and plans since the 1992 Rio Declarations to the launch of the 2019 Green Legacy campaigns. But in the face of diligence in the production of such policies by FDRE governments, at the local level, as in the four kebele in Northern and Southern Ethiopia researched ethnographically, there is no echo of longstanding climate policy. In the name of climate change, new labels have been given to old projects to support farmers in their daily lives. Indeed, this article intends to show how those plans and strategies are produced to remain as such and not become practices, and to intercept the acclaim and economic support of international climate governance.